Strategy to Improve Customer Awareness and Satisfaction Towards the Use of the PLN Mobile Application at PT PLN ULP Banjarbaru - Amanda Rita Rolanda; Alldila Nadhira Ayu Setyaning (Universitas KH. Abdul Chalim Mojokerto, 2026)
The rapid development of digital technology has encouraged public service companies to adapt by utilizing digital-based applications to improve service quality for customers. PT PLN (Persero), as the national electricity service provider, has introduced the PLN Mobile application as an integrated digital service platform. This study aims to analyze the level of customer awareness and satisfaction regarding the use of the PLN Mobile application at PT PLN (Persero) Unit Layanan Pelanggan (ULP) Banjarbaru.This research employs a qualitative approach using a case study method. Data were collected through observation, in-depth interviews with PLN officers and PLN Mobile users, as well as supporting documentation. Data analysis was conducted descriptively through the stages of data reduction, data presentation, and conclusion drawing.The results indicate that the level of customer awareness of the PLN Mobile application varies among users. Customers who received direct socialization and education from PLN officers demonstrated a better understanding of the application’s functions and benefits. Furthermore, the use of the PLN Mobile application has been shown to enhance customer satisfaction, particularly in terms of ease of service access, time efficiency, and convenience in conducting transactions and reporting power outages. However, several minor technical issues were still identified, such as delayed notifications and occasional system disruptions.Overall, the PLN Mobile application plays a positive role in improving customer satisfaction. Therefore, PT PLN ULP Banjarbaru is recommended to continuously enhance its socialization and education strategies and to further develop the application in order to optimize the utilization of digital services by customers.